The complete mitogenome of the giant clam Tridacna squamosa (Heterodonta: Bivalvia: Tridacnidae). (2nd September 2016) - Gan, Han Ming; Gan, Huan You; Tan, Mun Hua; Penny, Shane S.; Willan, Richard C.; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the commercially and ecologically important and internationally vulnerable giant clam Tridacna squamosa was recovered by genome skimming using the MiSeq platform. The T. squamosa mitogenome has 20, 930 base pairs (62.35% A+T content) and is made up of 12 protein-coding genes, 2 ribosomal subunit genes, 24 transfer RNAs, and a 2594 bp non-coding AT-rich region. The mitogenome has a relatively large insertion in the atp6 gene. This is the first mitogenome to be sequenced from the genus Tridacna, and the family Tridacnidae and represents a new gene order.